Microstructural characterisation of air plasma sprayed nanostructure ceramic coatings on Mg–1%Ca alloys (bonded by NiCoCrAlYTa alloy) - Daroonparvar, M. (Elsevier Ltd, 2016)
Nanostructured composite ceramic coatings consisting of Al2O3–13%TiO2 and Al2O3–13%TiO2/TiO2 on NiCoCrAlYTa-coated Mg alloys were sprayed using the atmospheric plasma spraying method. The composition and microstructure of the coated samples were investigated by XRD and FESEM equipped with EDS. Corrosion and wear behaviours of the coated samples were also evaluated. The results showed that Al2O3–13%TiO2/TiO2 coating is able to reduce the anodic dissolution of the Mg alloy in chloride solutions compared to other samples. The surface of the Al2O3–13%TiO2/TiO2 coating with the lowest wear rate exhibited a typical mild wear mode with narrow wear tracks along with very few small transferred particles. This observation was mainly related to the dense structure of the TiO2 coating, which could reduce severe spalling within the splats during the wear test.